2017
DOI: 10.3233/jad-170221
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference in Aerobic Exercise Efficacy to Improve Cognition in Older Adults with Vascular Cognitive Impairment: Secondary Analysis of a Randomized Controlled Trial

Abstract: Aerobic training (AT) is a promising, non-pharmacological intervention to mitigate the deleterious effects of aging and disease on brain health. However, a large amount of variation exists in its efficacy. This is a secondary analysis of a randomized controlled trial of AT in 71 older adults with subcortical ischemic vascular cognitive impairment (NCT01027858). Specifically, we investigated: 1) whether sex moderates the relationship between AT and executive functions, and 2) the role of brain derived neurotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
3
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 86 publications
2
62
3
2
Order By: Relevance
“…While BDNF levels are known to decline with age, this decline is associated with cognitive impairment in older females only (61). Recently, it was reported that circulating levels of BDNF increased in older females following 6 months of aerobic training, whereas it decreased in males (62). Oestrogen has also been associated with greater BDNF expression in the hippocampus and cortex of females (63,64).…”
Section: Discussionmentioning
confidence: 99%
“…While BDNF levels are known to decline with age, this decline is associated with cognitive impairment in older females only (61). Recently, it was reported that circulating levels of BDNF increased in older females following 6 months of aerobic training, whereas it decreased in males (62). Oestrogen has also been associated with greater BDNF expression in the hippocampus and cortex of females (63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have recently shown that 6 months of AT can indeed increase circulating levels of BDNF in the periphery in older women with mild subcortical ischemic vascular cognitive impairment, but decreases levels in men [124]. Thus, more studies focused on understanding the role of different exercise modalities on BDNF levels in women compared to men are required.…”
Section: Possible Role Of Hormones and Bdnf In Sex Differences In Exementioning
confidence: 97%
“…For example, studies indicate that exercise can offset cognitive decline with the type of exercise related to differential efficacy in men versus women [194] and indeed physical activity can increase hippocampal subregions differently in women versus men [195]. It is vital to understand what exercise regimen (or any type of treatment) may be more beneficial to men versus women to combat disease and agingrelated cognitive decline [194]. A number of studies demonstrate sex differences in associations between hippocampal adult neurogenesis and cognition.…”
Section: Future Directions and Clinical Implicationsmentioning
confidence: 99%